Perancangan Aplikasi Pencarian Guru Les Privat Komputer Berbasis Android - Nur Alam Arifin; Siti Marti’ah; Zaeid Akhmada Mustofa (Journal of Informatic and Information Security, 2020)
The purpose of this research is to help students get learning outside the school environment, this is a better education because in addition to school children also get education from private lessons. In addition, this application also functions as a forum for private tutors to boost the economy. Gathering the information students need to do computer learning which is currently all done is easier. So it is hoped that with the design of this private computer tutoring application, it can help students get learning outside the school environment and around the student's residence. The research method used is grounded research, which is a research method based on facts and uses comparative analysis with the aim of making empirical generalizations, establishing concepts, proving theories, developing theories, collecting and analyzing data at the same time. After the author analyzes and collects data, finally the writer can draw the conclusion that with this application system, it can help students get the learning they need easily and efficiently.